Fictions of embassy: literature and diplomacy in early modern Europe - Hampton, Timothy (Cornell Univ. Press, 2009)
Introduction : angels and pimps : toward a diplomatic poetics -- Words and deeds : diplomacy and humanist fiction -- The useful and the honorable : the ethics of mediation in the late Renaissance -- Epic and the law of nations : Tasso's Jerusalem delivered -- From Cortez to Camões : identity and authority in the discourse of discovery -- Big states and small states : sovereignty, diplomatic recognition, and the theater of Pierre Corneille -- Hamlet's diplomacy : state-building, dispatch, and revenge -- The tragedy of delegation : diplomatic action and tragic form in Racine's Andromaque -- Conclusion : in the Hôtel des Ambassadeurs